The Relationship between Consumer Preferences and Environmental Unconsciousness Towards Green Products - Lim, Jia Qi; Azizan, Anim Zalina (Research in Management of Technology and Business, 2025)
This research investigates the factors influencing consumers’ decisions to purchase green products, focusing on sustainable consumer behavior. It examines the roles of cultural, social, personal, and psychological factors in shaping purchase intentions using quantitative methods, including surveys and statistical analysis. The findings reveal that environmental awareness and personal values significantly drive green purchase intentions, with notable variations across demographic segments. These results highlight the importance of targeted marketing strategies and education initiatives for businesses and policymakers to promote green consumerism. Future research should explore the role of technology in enhancing sustainable purchasing decisions.